2021
DOI: 10.1186/s12875-021-01412-0
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study examining secondary prevention post stroke in primary care in an Asian setting

Abstract: Background Stroke is one of the top contributors to burden of disability-adjusted life-years worldwide. Family physicians have key role in optimising secondary prevention following stroke by managing clinical risk factors and promoting overall control in accordance with clinical practice guidelines. Methods Our objectives were: (i) to examine level of overall risk factor control together with control of singular risk factors one-year after an index… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
1
1
Order By: Relevance
“…Once stroke occurs, the regenerative potential decreases, and the inflammatory responses to this disease increase in the elderly [ 35 , 36 ]. Furthermore, we found that the proportion of stroke survivors aged < 60 years in our study was greater than that in a study conducted in Singapore [ 24 ]. This may be because Shenzhen is one of the most developed cities in China.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Once stroke occurs, the regenerative potential decreases, and the inflammatory responses to this disease increase in the elderly [ 35 , 36 ]. Furthermore, we found that the proportion of stroke survivors aged < 60 years in our study was greater than that in a study conducted in Singapore [ 24 ]. This may be because Shenzhen is one of the most developed cities in China.…”
Section: Discussioncontrasting
confidence: 85%
“…With the increasing prevalence of multiple chronic conditions (MCCs) in stroke survivors, MCCs have a modest association with post-stroke functional outcomes and contribute considerably to functional impairment [ 19 23 ]. In Singapore, a recent study confirmed the relationship between MCCs and post-stroke readmission [ 24 ]. A previous study published by our team also found that increased MCCs lead to poorerADL ability in older stroke survivors, although there were no data available on young stroke survivors [ 21 ].…”
Section: Introductionmentioning
confidence: 89%
“…No contexto de AVEi, a prescrição de agentes antiplaquetários, como o ácido acetilsalicílico, ou anticoagulantes, como a varfarina, é comumente indicada para reduzir o risco de eventos tromboembólicos recorrentes. Contudo, a decisão sobre o regime terapêutico específico deve levar em consideração fatores como a etiologia do AVE, comorbidades, riscos de sangramento e a presença de fibrilação atrial, sendo uma decisão personalizada para cada paciente (BANSAL;LEE;SMITH, 2021;FLACH et al, 2020).…”
Section: Estratégias Para Prevenção Secundáriaunclassified

Desafios no Tratamento de Idosos Vítimas de Acidente Vascular Encefálico

Analiane Barbosa Formiga Alves,
Luísa Lanny Leite Sales,
Anne Caroline Oliveira Nonato
et al. 2024
coopex
“…Several studies investigated the adherence of primary care settings to secondary stroke prevention guidelines. They revealed that many of these patients were not optimally treated according to guidelines, potentially due to the lack of a holistic, multidisciplinary and patient-orientated follow-up (Table 1 ) [ 74 80 ]. Accordingly, a secondary cardiovascular prevention study including patients with previous stroke followed-up in primary care demonstrated that only 53% of them were treated with statins, and 59% did not achieve the optimal BP, despite using antihypertensive treatment [ 81 ].…”
Section: The Primary Care Perspectivementioning
confidence: 99%